Can information constraints explain the low efficiency in premium quality rice cultivation? Evidence from smallholder farmers in Bangladesh - Kubitza, Christoph; Veettil, Prakashan Chellattan; Gupta, Ishika; Krupnik, Timothy J. (Wiley, 2024)
The integration of smallholder farmers into emerging value chains for fine-grain and aromatic ‘premium quality rice’ (PQR) could prove to be crucial to improving rural livelihoods in Bangladesh, though efforts could be constrained by farmers' differing levels of agronomic knowledge. Based on a pre-analysis plan, we analyse farmers' ability to efficiently allocate production enhancing inputs in PQR cultivation based on a survey of 1420 farmers in key PQR producing areas. Farmers received a hypothetical budget to allocate to six different inputs advised for efficient production of PQR, mimicking familiar production decisions made seasonally on their own farms. Our results suggest that even without budget or input access constraints farmers tend to inefficiently allocate inputs in PQR in this hypothetical setting. In particular, they tend to overspend on seeds, fertiliser and pesticides. Farmers with better access to agricultural information, such as through PQR specific extension services, conversely reach substantially higher efficiency scores and decided to spend significantly less on fertiliser. Without future adjustments such as more targeted extension services, implied higher production costs will likely lower the profitability of PQR cultivation for smallholder farmers, thereby limiting potential income gains. Besides these economic concerns, excessive input use is associated with environmental externalities. Improved efficiency is therefore desirable from both an economic and environmental standpoint.